Shifting Baselines of Europe New Perspectives beyond Neoliberalism and Nationalism - Büllesbach, Daphne; Cillero, Marta; Stolz, Lukas (X-Texte zu Kultur und Gesellschaft, 2017)
This book opens the often narrow discourse on the future of Europe and criticises the false dichotomy between nationalism on the one hand and a neoliberal version of Europe on the other. Existing emancipatory projects from across the continent are presented together with reflections on strategies to achieve a democratic Europe beyond the nation state: from the municipal level to the level of transnational media, from technology and counter-surveillance to the systemic change provided by the commons movement and more. The shift towards a new way of thinking and doing politics is possible! With contributions by Etienne Balibar, Ulrike Guérot, Gesine Schwan, Renata Avila, Barbara Spinelli, Andreas Karitzis, Lorenzo Marsili, Jonas Staal, among others, and interviews with city governors from Madrid to Naples. ''"Anyone interested in survival in today's Europe, should read this book." - Srecko Horvat, Philosopher, DIEM25 ''"The ideas and projects presented in this book are exactly what the debate on Europe needs right now." - Saskia Sassen, Professor of Sociology, Columbia University